The Influence Of Organizational Culture And Organizational Commitment On Character Formation Of Members Of The Cilamaya Village Youth Organization - Dawam Muhammad Fadlun; Sari Marliani; July Juliawaty (International Journal of Management, Economic, Business and Accounting, 2025)
Purpose of the study — This research aims to examine the influence of organizational culture and organizational commitment on the character formation of Karang Taruna members in Cilamaya Village. Research method— The study was conducted at the Cilamaya Village Youth Organization in Cilamaya Wetan District, Karawang Regency, involving 52 members. A quantitative descriptive and verification method was employed, utilizing SPSS 25 for analysis. Result— The findings indicate that organizational culture (X1) does not have a significant influence on character formation, with a significance value of 0.409 (> 0.05) and a t count of 0.832 (< 1.676). Conversely, organizational commitment shows a very significant influence on character formation, with a significance value of 0.000 (< 0.05) and a t count of 5.615 (> t table 1.676). Moreover, when assessed simultaneously, both organizational culture and organizational commitment significantly influence character formation, with a significance value of 0.000 (< 0.05) and an F count of 45.742 (> F table 4.04) Conclusion— It is suggested that through training or workshops, the character formation of Karang Taruna members in Cilamaya Village can be further improved.